Determinants of MSME Performance in Karawang Regency - Ferina, Lia; Widyaningsih, Dewi (Penerbit Goodwood, 2025)
Purpose: The objective of this research is to determine the impact of financial literacy, fiscal intensification, financial capital, and digital adoption on MSME business performance in Karawang Regency. Methodology/approach: A quantitative method was applied in this study using a survey of 60 respondents. The collected data were processed with IBM SPSS Statistics 25 software, employing multiple linear regression along with validity, reliability, and classical assumption testing. Results/findings: Based on the analysis, all research instruments were proven valid and reliable, and the data were normally distributed, heteroscedastic, and free from multicollinearity issues. Each of the four independent variables shows a positive and significant effect on MSME business performance, where digital usage has the highest influence, with a regression coefficient of 0.679. Conclusions: The findings indicate that the combined influence of financial literacy, fiscal intensification, financial capital, and digital adoption significantly enhances MSME business performance. Among these, digital adoption plays the most dominant role, indicating that embracing technology is key to improving competitiveness and business growth. Limitations: Despite the fact that numerous other factors also affect MSME performance, only four variables were used. Additionally, the short study duration makes it impossible to record long-term changes in MSME company dynamics, and the use of a closed-ended questionnaire may induce subjective bias. Contribution: It is projected that this research will generate new contributions to the scientific development of financial management and entrepreneurship while offering a clearer understanding of the key factors impacting MSME performance in the digital age.